2004
DOI: 10.1038/sj.jea.7500358
|View full text |Cite
|
Sign up to set email alerts
|

Variability of personal chemical exposure in eight office buildings in Sweden

Abstract: This study focuses on the variability in chemical exposures for individuals working in office buildings. The study involved eight office buildings with 79 participants, and exposures were measured using personal samplers for volatile organic compounds, aldehydes, amines, nitrogen dioxide, ozone, and particles. Ventilation was assessed in each individual office. ''Variability among buildings'' and ''variability among individuals'' were evaluated for any component (of the 123) measured in samples from at least 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 25 publications
(27 reference statements)
0
22
1
Order By: Relevance
“…These differences may have affected measured concentrations, since we know that the variability within buildings for most compounds is fairly large (Glas et al 2004), and the time and where time is spent affect exposure. The differences do not discriminate between people with and without symptoms.…”
Section: D-limonenementioning
confidence: 98%
See 2 more Smart Citations
“…These differences may have affected measured concentrations, since we know that the variability within buildings for most compounds is fairly large (Glas et al 2004), and the time and where time is spent affect exposure. The differences do not discriminate between people with and without symptoms.…”
Section: D-limonenementioning
confidence: 98%
“…The chemicals the participants were exposed to during a workweek were sampled with diffusive samplers carried on a specially designed vest (Glas et al 2004), ensuring that their placing was the same on all participants. Participants were instructed to open the samplers when they arrived at their work, and close them when they left the building.…”
Section: Sampling and Chemical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Concentrations of total VOC (TVOC) in office buildings commonly range between less than 100 µg/m 3 and several thousand micrograms per cubic meter, but maximum values of up to 50,000 µg/m 3 have been reported (11,12). More than 350 VOCs have been detected at concentrations exceeding 1 ppb in indoor air (3), but generally only about 30 to 70 are routinely measured and even fewer are consistently detected in a majority of office buildings (12)(13)(14)(15). When a group of Nordic scientists reviewed the literature up to early 1996 regarding VOC/ TVOC and health, they concluded that neither exposure nor epidemiological studies provided conclusive evidence that TVOC provided a risk index for health and comfort effects in buildings (11).…”
Section: Volatile Organic Compoundsmentioning
confidence: 99%
“…The most striking finding was that the same factors were associated with different symptoms and the same symptoms were associated with different factors in the various buildings. Furthermore, a recent comparison of personal exposures (measured in the breathing zone of individual subjects) to aldehydes, amines, NO 2 , O 3 , particles, and VOCs in eight office buildings in a town in northern Sweden found that intra-individual differences accounted for the variation of 78% of the 123 measured compounds, whereas differences among buildings were the major source of variability for only 14% of the compounds (13). This highlights the inadequacy of a few stationary measurements in buildings and underscores the need for personal exposure measurements.…”
Section: Exposures Vary Considerably Within Largementioning
confidence: 99%